Studi Kasus: Babesiosis (Piroplasmosis) disertai Infestasi Caplak yang Berat pada Anjing Gembala Jerman - Amar Wira; I Wayan Batan; Sri Kayati Widyastuti; Hendro Sukoco (Jurnal Sains dan Teknologi Peternakan, 2020)
Babesiosis is a parasitic disease in red blood cells due to protozoan infection of the genus Babesia which is transmitted through tick vectors. A 5-years-old male German shepherd had decreased appetite, weakness, and infestation of ticks throughout his body. Clinical examination showed Capillary Refill Time (CRT) <2 seconds, pale mouth mucosa, erythema throughout the body, philtrum was dry and slow skin turgor. The results of a complete blood examination of the dog had hyperchromic microcytic anemia and lymphocytopenia, while the results of blood smear showed the existence of intraerythrocyte inclusion bodies. The dog was diagnosed with Babesiosis and treated with Ringer Lactate fluid therapy, administration of Clindamycin (25mg/kg BW; PO), Oxytetracycline (15mg/kg BW; PO), Anti-inflammatory Dexamethasone (0.5-1mg/kg BW; PO) and Hematodine (1ml/5kg BB; IV) given for seven days. After treatment, the dog has increased appetite and after 14 days shows improvement in clinical signs.